Genome-Wide Association Study Identifies NBS-LRR-Encoding Genes Related with Anthracnose and Common Bacterial Blight in the Common Bean - Wu, Jing; Zhu, Jifeng; Wang, Lanfen; Wang, Shumin (Frontiers in Plant Science, 2017)
Nucleotide-binding site and leucine-rich repeat (NBS-LRR) genes represent the largest class of disease resistance genes in plants. The genome sequence of common bean (Phaseolus vulgaris L.) provides valuable data for determining the genomic organization of NBS-LRR genes. However, data on the NBS-LRR genes in common bean are limited. A total of 178 NBS-LRR-type genes and 145 partial genes (with or without a NBS) located on 11 common bean chromosomes were identified from the common bean genome database. Nucleotide-binding site and leucine-rich repeat (NBS-LRR) genes represent the largest and most important disease resistance genes in plants. The genome sequence of the common bean (Phaseolus vulgaris L.) provides valuable data for determining the genomic organization of NBS-LRR genes. However, data on the NBS-LRR genes in the common bean are limited. In total, 178 NBS-LRR-type genes and 145 partial genes (with or without a NBS) located on 11 common bean chromosomes were identified from genome sequences database. Furthermore, 30 NBS-LRR genes were classified into Toll/interleukin-1 receptor (TIR)-NBS-LRR (TNL) types, and 148 NBS-LRR genes were classified into coiled-coil (CC)-NBS-LRR (CNL) types. Moreover, the phylogenetic tree supported the division of these PvNBS genes into two obvious groups, TNL types and CNL types. We also built expression profiles of NBS genes in response to anthracnose and common bacterial blight using qRT-PCR. Finally, we detected nine disease resistance loci for anthracnose (ANT) and seven for common bacterial blight (CBB) using the developed NBS-SSR markers. Among these loci, NSSR24, NSSR73, and NSSR265 may be located at new regions for ANT resistance, while NSSR65 and NSSR260 may be located at new regions for CBB resistance. Furthermore, we validated NSSR24, NSSR65, NSSR73, NSSR260, and NSSR265 using a new natural population. Our results provide useful information regarding the function of the NBS-LRR proteins and will accelerate the functional genomics and evolutionary studies of NBS-LRR genes in food legumes. NBS-SSR markers represent a wide-reaching resource for molecular breeding in the common bean and other food legumes. Collectively, our results should be of broad interest to bean scientists and breeders.